2017
DOI: 10.1177/0267659117715506
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-coated cardiopulmonary bypass circuit attenuates upregulation of both proteases/protease inhibitors and platelet degranulation in pigs

Abstract: The new polymer (SEC)-coated CPB circuit effectively attenuated upregulation of proteins compared to the non-coated CPB circuit. These proteins were associated with both proteases/protease inhibitors and platelet degranulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…They demonstrated that the SEC-coated circuit has biocompatibility equivalent to that of the PMEA-coated circuit, with no significant differences in coagulation or inflamma-tion during CPB. Suehiro et al 4 demonstrated in a pig model of CPB that the SEC-coated circuit effectively attenuated the upregulation of proteins related to platelet degranulation. This study showed that the heparin dose and subsequent protamine dose were significantly higher in the SEC-coated circuit than those in the heparin-coated circuit as will be understood.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that the SEC-coated circuit has biocompatibility equivalent to that of the PMEA-coated circuit, with no significant differences in coagulation or inflamma-tion during CPB. Suehiro et al 4 demonstrated in a pig model of CPB that the SEC-coated circuit effectively attenuated the upregulation of proteins related to platelet degranulation. This study showed that the heparin dose and subsequent protamine dose were significantly higher in the SEC-coated circuit than those in the heparin-coated circuit as will be understood.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 However, with respect to the membrane oxygenator, several reports have suggested that ACP coating could neutralize cell adhesion and adsorption. 16,26 Based on these reports, significant differences should have been observed Experimental solution comprising albumin, lysozyme, and vancomycin was continuously stirred in a reservoir. In addition, it was continuously circulated in the circuit including a membrane by a roller pump (positioned lower) at a flow rate of 200 mL/min and was continuously filtered by another roller pump (positioned higher) at a flow rate of 50 mL/min.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to adsorption of low-molecular-weight peptide compounds, the vancomycin results suggest two possibilities: ACP coating could inhibit peptide compound adsorption, and in the case of the non-coated membrane, the adsorption would be completed in the initial 15 min. With respect to ACP coating, the absence of protein adsorption has been reported, 16,26 but the adsorption of peptide compounds such as enzymes and/or antibiotics has not been clarified. Vancomycin, a glycopeptide antibiotic with a molecular weight of 1495 Da, has a structure similar to that of enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The anesthetic and experimental procedures were performed as described previously. 13 In brief, 12 domestic juvenile pigs (body weight = 16 kg) were randomized into two groups: the normothermic (37°C) CPB group and hypothermic (23°C) CPB group (n = 6, respectively). After an overnight fast with free access to water, animals were premedicated by intramuscular injection of ketamine (20 mg/kg), xylazine (3 mg/kg), and 0.5 mg of atropine.…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported that a polymer-coated CPB circuit attenuated upregulation of proteins in both proteases/ protease inhibitors and platelet degranulation. 13 The aim of this study was to verify whether deep hypothermic CPB could reduce upregulation of blood proteins activated by contact with a polymer-coated CPB circuit in juvenile pigs.…”
Section: Introductionmentioning
confidence: 99%